-7x - 2y = -3
3x + 2y = 7
The standard form is 7x + 2y - 3 = 0
3x = 2y + 7 The standard form is: 3x - 2y - 7 = 0
This means that 2y - 3 = 2y + 4 which is not possible.
It is: y = x+5 in y = mx+b form
If: -3x+2y = 12 Then: y = 1.5x+6 in slope-intercept form
y = -2x+10
Slope Intercept form) Y=0.5X=3
y = -0.5x + 5
It is: y = -3.5x+2.5 in slope-intercept form
4x+2y = 20 2y = -4x+20 y = -2x+10
3x+2y = 1 2y = -3x+1 y = -1.5x+0.5
If: 5x+2y = 9 Then: y = -2.5x+4.5 in slope intercept form
2y+26 = 28 2y = 28-26 2y = 2 y = 1
x = 11 - 2y and 14 - 2y. This means that 11 = 14. Is there a typo in the question?
It is: y = -2.5x-2
-2y=x+8 is the answer
Exactly (2y + 4) .
No 2y-3 is not equals y plus 2AND how old are u?